Appropriate Technology (TTG) as a Solution by KKN Students in Sambibulu Village : A Smart Waste Place: Teknologi Tepat Guna (TTG) Sebagai Solusi Oleh Mahasiswa Mahasiswi KKN di Desa Sambibulu : Tempat Sampah Pintar - Waradhani , Farra Dwi Susilo; Purwanto , Syilviana Eka; Palupi , Ririn Retno; Aristanti , Prigi Dwi Gita; Sari, Indah Apriliana (Procedia of Social Sciences and Humanities, 2022)
Disposing of garbage in its place can also be part of protecting the environment, but awareness of this is still relatively low. In tourist attractions, awareness is needed to maintain cleanliness, one of which is by throwing garbage in its place, because this will affect the beauty of the tourist spot itself. The goal in making Appropriate Technology in the form of smart trash cans equipped with motion sensors is to increase public interest in disposing of waste in its place. Smart trash cans that are designed and assembled have their own added value because they can increase public interest in disposing of waste in its place. The sensor trash bin can also make it easier when you want to throw out trash because you don't need to touch it anymore and just be in front of it, it will automatically open. The method used in this journal is descriptive qualitative. The data collection method was carried out by observation and interviews with several communities in Sambibulu Village. The results we got after the creation of smart trash bins were completed, the villagers were interested and started to get used to throwing garbage not just anywhere.